Postfeminism and Contemporary Hollywood Cinema
XII, 257 p.
Keywords: By analyzing the negotiation of femininities and masculinities within contemporary Hollywood cinema, Postfeminism and Contemporary Hollywood Cinema presents diverse interrogations of popular cinema and illustrates the need for a renewed scholarly focus on contemporary film production.